Spatial interaction healthcare accessibility model – an application to Texas - de Mello-Sampayo, F. (Applied Spatial Analysis and Policy, 2018)
A theoretical model was developed using the entropy approach to cope with the random component of the utility function to find that the spatial accessibility improves as the provider capacity increases or the opportunity cost of traveling to and from health provider decreases. The Kernel Density Estimation of the model show disparities in healthcare accessibility with extensive pockets of poor accessibility in rural and peripheral areas in Texas, when using hospitals' location and number of hospital beds or counties' centroid and data on Primary Care Physician. The model can be beneficially used to evaluate policies indicative of changes in the provision of health services, such as closures of rural hospitals or capacity increases, potentially have spatially very differentiated accessibility outcomes.